The rhetoric of the interrogative sentence and its artistic aesthetics (Journal of the College of Basic Education, 2023)
The interpositional sentence is a sentence that is subject to double interpretation according to the structural context in which it appears. It is either multiple semantics, or it is empty of semantic content. It changes with the change of the topic and the context in which it is driven. In many cases, it is a sentence that carries moral richness in transforming hypostases that serve both sides of the process of message and creativity, and they are all From the creative poet and educated reader who deciphers closed codes.It is known that the objection is one of the rhetorical arts that fall within the investigations of the science of meanings, which looks at the details of the Arabic sentence and the changes that occur to it, such as deletion, introduction and delay, or separation and linking, because the objection is one of the many methods of verbosity that rhetoricians mention in their works.As for my reading of this rhetorical style, it is an aesthetic reading that examines the technicalities of its content, and its rhetorical impact affected by various social, environmental and spatial transformations, by the diversity of the concerns of society and the concerns of its expatriate poets, psychological alienation and spatial alienation. The sentence intercepts the text read and other sentences in it (such as the verbal and the nominal), and reserves the element of succession in ideas to create a new idea that may go along with the text, or give it a connotation that agrees with, or contradicts the text, because it appears in the intensity of the text to limit it a little and its intensity, or to increase its turmoil and turmoil. So it deviates from the typical and positivist connotations that critics and rhetoricians put in place, such as interpretation, explanation, and emphasis, and puts new connotations in the text that grammarians did not pay attention to in grammar science, and they did not find in it any meanings that would serve them, so they closed and locked the doors on it with two explanations that narrowed it down and limited its work, so it was only a sentence for them. The relative link or a sentence that has no place in the inflection and is contingent and can be considered an extra sentence, and they justified themselves deleting it and getting rid of it, as it is an obstacle to their current work Hawi is strict in its complexity.